A Colonic Perineurioma - Tomoyuki Otani; Kinta Hatakeyama; Emi Ohtani; Susumu Nakayama; Takashi Fujimoto; Chiho Ohbayashi (SAGE Publishing, 2018)
Perineurioma is a mesenchymal neoplasm best known in soft-tissue pathology. A colonic perineurioma is a relatively recently described entity and sometimes encountered in specimens from the large intestine, especially distal colon. Without its recognition, a perineurioma can be misdiagnosed as other more common gastrointestinal spindle cell neoplasms. Here, we describe a case of colonic perineurioma with polypoid growth extruding into the intestinal lumen. Case. A woman in her seventh decade of life underwent a follow-up colonoscopy after an uneventful resection of a benign colonic polyp. A previously undetected 6-mm polyp was found in the sigmoid colon and was resected endoscopically. Microscopic examination of the lesion revealed a proliferation of bland spindle cells in the lamina propria mucosae, which were immunohistochemically positive for epithelial membrane antigen, claudin 1, and glucose transporter-1. A colonic perineurioma was diagnosed.